Science and religion in Montesquieu's thought: The scientific foundation of the religious Enlightenment. - Ming, Chong (Chinese Studies in History)
A defining feature of the religious Enlightenment in eighteenth-century Europe was the justification of religion through science and reason. In his explorations of natural science, Montesquieu sought to demonstrate the independence of nature from God and to distinguish between science and religion, thereby defending science and the scientific spirit. Simultaneously, drawing on the regularity of cosmic operations and the complexity of the human body revealed by modern science, Montesquieu employed the design argument to deduce the existence of a rational deity and accepted deism. He further posited that reason, sentiment, and faith constitute the three pathways through which humans approach religion, arguing that beyond natural religion, humanity still requires revealed religion. Through his analysis of the complex relationship between science and religion, Montesquieu, while constructing and defending the scientific spirit, justified both natural and revealed religion, thereby laying the scientific foundations for the religious Enlightenment.